2021
DOI: 10.1016/j.jbc.2021.100291
|View full text |Cite
|
Sign up to set email alerts
|

Androglobin gene expression patterns and FOXJ1-dependent regulation indicate its functional association with ciliogenesis

Abstract: Androglobin (ADGB) represents the latest addition to the globin superfamily in metazoans. The chimeric protein comprises a calpain domain and a unique circularly permutated globin domain. ADGB expression levels are most abundant in mammalian testis, but its cell-type-specific expression, regulation, and function have remained unexplored. Analyzing bulk and single-cell mRNA-Seq data from mammalian tissues, we found that—in addition to the testes—ADGB is prominently expressed in the female reproductive tract, lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 66 publications
6
28
0
Order By: Relevance
“…Moreover, a recent study reported the consistent presence of Adgb in the ciliomes of three distinct evolutionary ancestral taxa, further suggesting a conserved function related to microtubular organisation and likely flagella formation (Sigg et al 2017). In line with this study, our recent in vitro investigations have demonstrated that Adgb is transcriptionally regulated by FoxJ1, a master regulator of ciliogenesis (Koay et al 2021).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, a recent study reported the consistent presence of Adgb in the ciliomes of three distinct evolutionary ancestral taxa, further suggesting a conserved function related to microtubular organisation and likely flagella formation (Sigg et al 2017). In line with this study, our recent in vitro investigations have demonstrated that Adgb is transcriptionally regulated by FoxJ1, a master regulator of ciliogenesis (Koay et al 2021).…”
Section: Discussionsupporting
confidence: 85%
“…Decreased mRNA expression levels in infertile versus fertile men (Platts et al 2007) suggest a potential role of Adgb in spermatogenesis. Gene regulation and expression studies further suggest an association of Adgb with ciliogenesis including flagellum formation (Koay et al 2021). However, the in vivo function of Adgb remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we speculate that the Adgb and FAP42 have similar position within C1b/C1f supercomplex. Importantly, in mammals androglobin is expressed at higher level in cells assembling motile cilia and its expression is co-regulated by FOXJ1 24 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Jund has been reported to be involved in multiple mechanisms of cell fate regulation in the lung, including mediating transcriptional activation of angiotensinogen ( Abdul-Hafez et al, 2009 ), inducing interleukin-6 ( Eickelberg et al, 1999 ), and participating in lung carcinogenesis ( Ruiz et al, 2021 ). Foxj1 affects the differentiation and functional performance of ciliated cells distributed throughout the airway tree, including the trachea, lobar bronchi, and terminal bronchiole ( You et al, 2004 ; Koay et al, 2021 ). Hcfc1 drives cell-cycle gene expression as a transcriptional regulator, depending on heat-shock proteins 90 ( Antonova et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%